Biografia e trajetória de uma elite judicial: os profissionais anticorrupção brasileiros - Trombini, Maria Eugenia; Jorge, Mario; Valarini, Elizângela (Revista de ciências socíais, 2022)
Who are the professionals working on anti-corruption issues in Brazil? Based on a database of interviews with lawyers, judges and prosecutors experienced in corruption cases, we applied a prosopographical method to describe the social, educational and occupational dimensions of the group. Our results show that the volume of investment in education exceeds that of other legal careers outside the economic criminal specialty, that public universities remain the preferred choice of this legal elite, and that stays abroad are as frequent as post-graduate studies at local schools. To assist the research agenda on Law and Society as well as Law and Politics, we investigate the different colorations of professionals that occurred in the database.